2009
DOI: 10.1111/j.1365-2982.2009.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rapid swallowing: a complementary test during standard oesophageal manometry

Abstract: Multiple rapid swallowing (MRS) stimulates neural inhibition resulting in abolition of contractions in the oesophageal body (OB) and complete lower oesophageal sphincter (LOS) relaxation which is followed by peristalsis and LOS contraction. The aim of this study was to evaluate the yield of MRS to detect abnormalities in inhibitory or excitatory oesophageal mechanisms in patients with oesophageal symptoms and either normal standard manometry or ineffective oesophageal motility (IOM). MRS (five water swallows, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
188
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(205 citation statements)
references
References 35 publications
12
188
1
4
Order By: Relevance
“…4). Conversely, in other instances, diagnosis might be achieved via minimal bolus flow time ascertained during high-resolution impedance mano metry 28,29 , a timed barium oesophagram 26 , or a rapid drink challenge 30,31 . However, in most cases an IRP >15 mmHg will suffice to detect impaired EGJ relaxation.…”
Section: Normal Irp Achalasiamentioning
confidence: 99%
“…4). Conversely, in other instances, diagnosis might be achieved via minimal bolus flow time ascertained during high-resolution impedance mano metry 28,29 , a timed barium oesophagram 26 , or a rapid drink challenge 30,31 . However, in most cases an IRP >15 mmHg will suffice to detect impaired EGJ relaxation.…”
Section: Normal Irp Achalasiamentioning
confidence: 99%
“…We adopted the MRS test because it is cheap and easy-to-execute and to interpret, allowing a widespread utilization as a complementary test during HRM. 17 Overall, we consider the current MRS test Finally, a study performed by means of magnetic resonance showed that reflux volume is higher than 5-10 mL of water administered during a standard HRM protocol study. 39 For this reason, the esophageal contraction after a multiple rapid sequence of swallows may better represent the motor contraction elicited after a gastro-esophageal reflux event.…”
Section: Discussionmentioning
confidence: 99%
“…With multiple rapid swallows (MRS), five 2 ml water swallows are administered 2-3 s apart [30,31], while with multiple water swallows (MWS), 200 ml of water is drunk freely [26•, 32]. The response to both tests in normal individuals is augmentation of deglutitive inhibition leading to complete LES relaxation and termination of peristalsis in the esophageal body.…”
Section: Adjunctive Testingmentioning
confidence: 99%